Anti-dandruff composition and preparation method and application thereof
The anti-dandruff compositions prepared by synergistically prepared by β-glucan, carboxymethyl chitosan, thresorbent polysaccharide, pyridone ethanolamine salt and PCA zinc have solved the shortcomings of existing hair care products in oil control and dandruff control, achieving oil control and dandruff control effects deep into the hair.
Patent Information
- Application Number
- CN202411983559.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-08
AI Technical Summary
Existing hair care products have shortcomings in oil control and anti-dandruff. Traditional oil control products cause harm to hair. Anti-dandruff products are not effective and are prone to recurrence of dandruff.
Anti-dandruff compositions prepared by synergistically prepared by β-glucan, carboxymethyl chitosan, thresorbent polysaccharide, pyridone ethanolamine salt and PCA zinc are penetrated deep into the hair through their good surfactivity and ability to dissolve bacterial outer membranes to achieve oil control and anti-dandruff effects.
The anti-dandruff composition can penetrate deep into the hair, improve utilization, significantly improve oil control and anti-dandruff effects, and reduce the risk of dandruff recurrence.
Smart Images

Figure BDA0005222048740000051 
Figure BDA0005222048740000061 
Figure BDA0005222048740000062
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of hair care products, in particular to an anti-dandruff composition and a preparation method and application thereof. Background Art
[0002] With the improvement of the quality of life, people pay more and more attention to themselves, from clothing to body shape, from the inside to the outside, all of which show the improvement of the focus on the self. Changes in the pressure environment of life, when our human health changes, such as imbalanced hormone secretion, mental stress, seasonal changes, excessive growth of fungi, etc., the metabolism of scalp keratin will be abnormal, the division of keratinocytes will be accelerated, and the replacement time of keratinocytes will be significantly shortened. The new replacement cells promote the rupture of the layered structure of the original old keratinocytes, so that the keratinocytes in pieces and blocks are detached and fall off, forming dandruff visible to the naked eye. The biggest impact on us is that various hair problems occur at the same time, such as greasy, dandruff, changes in hair quality, etc. Traditional oil-control hair care products use (1) substances containing alcohol, isopropyl alcohol, AHA and its derivatives, aluminum salts, etc. to control oil in the hair, but while controlling oil, they also cause more damage to the hair and affect the hair quality; dandruff removal products use (2) substances containing sulfur, coal tar, selenium disulfide, climbazole, etc. to remove dandruff in the hair, but they often fail to achieve the best dandruff removal effect when combined with other ingredients and only stay on the surface, which easily leads to recurrence of dandruff. In addition, existing shampoo products only stay on the hair surface scales and cortex, and cannot efficiently absorb the effective ingredients of natural plants, resulting in low utilization rate, poor absorption, poor hair care effect, and easy to be affected by environmental factors such as light.
[0003] Therefore, a hair care product with good absorption, oil control, hair care and anti-dandruff effects has broad application prospects. Summary of the invention
[0004] Based on this, the purpose of the present invention is to overcome the shortcomings of the above-mentioned prior art and provide an anti-dandruff composition with good absorption, oil control, hair care and anti-dandruff effect, as well as a preparation method and application thereof.
[0005] To achieve the above-mentioned purpose, the technical scheme adopted by the present invention is: an anti-dandruff composition, comprising the following components in parts by weight: 0.13-0.15 parts of β-glucan, 0.0001-0.005 parts of carboxymethyl deacetylated chitosan, 0.0001-0.005 parts of tremella polysaccharide, 0.4-0.6 parts of pyridone ethanolamine salt, and 0.12-0.15 parts of PCA zinc.
[0006] The anti-dandruff composition prepared by the synergistic combination of β-glucan, carboxymethyl chitosan, tremella polysaccharide, pyridone ethanolamine salt and PCA zinc can penetrate into the hair when used, and has a high utilization rate. The above components synergistically have good oil control, hair care and anti-dandruff effects. The anti-dandruff composition prepared by the synergistic combination of β-glucan, carboxymethyl chitosan and tremella polysaccharide has good surface activity, can dissolve the bacterial outer membrane, thereby promoting the destruction of bacteria (especially Gram-negative bacteria) by lysozyme, thereby increasing the anti-dandruff effect.
[0007] Preferably, the weight ratio of the carboxymethyl deacetylated chitosan to Tremella fuciformis polysaccharide is (2-3):1.
[0008] The inventors found in actual experimental processes that the weight ratio of carboxymethyl deacetylated chitosan and tremella polysaccharide has a great influence on the oil control, hair care and anti-dandruff effects of the final anti-dandruff composition. When the weight ratio of carboxymethyl deacetylated chitosan and tremella polysaccharide is within the above range, the oil control, hair care and anti-dandruff effects are better.
[0009] Preferably, the anti-dandruff composition further comprises the following components in parts by weight: 0.3-0.5 parts of guar hydroxypropyltrimethylammonium chloride, 0.05-0.07 parts of acrylic acid (ester) / acrylamide copolymer, and 0.07-0.09 parts of sodium hyaluronate.
[0010] Preferably, the anti-dandruff composition further comprises the following components in parts by weight: 0.4-0.5 parts of guar hydroxypropyltrimethylammonium chloride, 0.07 parts of acrylic acid (ester) / acrylamide copolymer, and 0.07 parts of sodium hyaluronate.
[0011] The present invention selects a system of guar gum hydroxypropyltrimethylammonium chloride, acrylic acid (ester) / acrylamide copolymer, and sodium hyaluronate as a thickener. The inventors found in actual experiments that when the above three specific components are selected as the thickening system, the oil control, hair care, and anti-dandruff effects of the anti-dandruff composition can be better exerted.
[0012] In addition, the present invention provides the use of the anti-dandruff composition in preparing hair care products.
[0013] Furthermore, the present invention provides a hair care product, which comprises the following components in parts by weight per 100 parts by weight:
[0014] Phase A: deionized water to make up to 100 parts by weight of each phase, 10-20 parts by weight of surfactant;
[0015] Phase B: 0.4-0.6 parts of ethylene glycol distearate;
[0016] Phase C: 0.3-0.5 parts of guar hydroxypropyltrimonium chloride, 0.05-0.07 parts of acrylic acid (ester) / acrylamide copolymer, 0.07-0.09 parts of sodium hyaluronate, 0.04-0.06 parts of polyquaternium-10, 0.08-0.12 parts of dipotassium glycyrrhizinate, 0.4-0.6 parts of p-hydroxyacetophenone, and 0.08-0.12 parts of phenoxyethanol;
[0017] Phase D: 0.2-0.4 parts of sodium chloride;
[0018] Phase E: 0.009-0.012 parts of quaternary ammonium salt-73, 0.0009-0.0012 parts of lactobacillus / soy milk fermentation product filtrate, 0.0009-0.0012 parts of purslane (PORTULACA OLERACEA) extract, 0.0009-0.0012 parts of Centella asiatica (CENTELLA ASIATICA) leaf extract;
[0019] Phase F: 0.13-0.15 parts of β-glucan, 0.0001-0.005 parts of carboxymethyl deacetylated chitosan, 0.0001-0.005 parts of tremella polysaccharide, 0.4-0.6 parts of pyridone ethanolamine salt, and 0.12-0.15 parts of PCA zinc.
[0020] Preferably, the surfactant in phase A is at least one of sodium laureth sulfate, cocamide MEA, sodium lauroyl sarcosinate, sodium C14-16 olefin sulfonate, sodium stearoyl lactylate, and sodium lauroyl sarcosinate; preferably, the surfactant in phase A is a mixture of sodium laureth sulfate, cocamide MEA, sodium C14-16 olefin sulfonate, sodium stearoyl lactylate, and sodium lauroyl sarcosinate, and the weight ratio is sodium laureth sulfate: cocamide MEA: sodium C14-16 olefin sulfonate: sodium stearoyl lactylate: sodium lauroyl sarcosinate = (10-15): (0.8-1.2): (0.4-0.7): (0.08-0.11): (0.08-0.11).
[0021] In addition, the present invention provides a method for preparing the hair care product, comprising the following steps:
[0022] (1) Add the raw materials of phase A into the emulsifying pot, heat to 85±2℃, turn on the homogenizer, speed 20-30 rpm, time 3-5min, keep warm and stir until completely dissolved.
[0023] (2) Add the raw materials of phase B into the emulsifying pot, stir and heat to 85±2℃, turn on the homogenizer, speed 20-30 rpm, time 3-5 min, keep warm and stir until completely dissolved.
[0024] (3) Add the Phase C raw materials into the emulsifying pot, stir and heat to 75±2℃, turn on the homogenizer, speed 20-30 rpm, time 3-5 min, keep warm and stir until completely dissolved.
[0025] (4) Add the phase D raw materials into the emulsifier, stir and heat to 65±2℃, turn on the homogenizer, speed 20-30 rpm, time 3-5 min, keep warm and stir until completely dissolved.
[0026] (5) Add the raw materials of phase E into the emulsifying pot, cool down and stir to 55±2℃, turn on the homogenizer, speed 20-30 rpm, time 3-5 min, keep warm and stir until completely dissolved.
[0027] (6) Add the phase F raw materials into the emulsifier, cool down and stir to 45±2℃, turn on the homogenizer, speed 20-30 rpm, time 3-5 min, keep warm and stir until completely dissolved.
[0028] (7) Cool down to room temperature, inspect, unload and can.
[0029] Compared with the prior art, the beneficial effects of the present invention are as follows: the anti-dandruff composition prepared by the synergistic combination of β-glucan, carboxymethyl deacetylated chitosan, tremella polysaccharide, pyridone ethanolamine salt and PCA zinc can penetrate deeply into the hair when used, and has a high utilization rate. The above components synergistically have good oil control, hair care and anti-dandruff effects. DETAILED DESCRIPTION
[0030] In order to better illustrate the purpose, technical scheme and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments. Its purpose is to understand the content of the present invention in detail, rather than to limit the present invention. All other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Unless otherwise specified, the experimental reagents and instruments designed for the implementation and comparative examples of the present invention are all commonly used ordinary reagents and instruments, which can be obtained from commercial channels. In the implementation and comparative examples, the experimental methods used are conventional methods unless otherwise specified; and unless otherwise specified, the raw materials used in parallel experiments are the same batch of raw materials.
[0031] The raw materials of the embodiments and comparative examples of the present invention are further described, but are not limited to the following raw materials. The rest of the raw materials not specifically described are all conventionally available on the market:
[0032] β-Glucan: BASF;
[0033] Pyridone ethanolamine salt: Yantai Dongfang Chemical Co., Ltd.;
[0034] PCA zinc: Shanghai Huanqiu Industrial Development Co., Ltd.;
[0035] Carboxymethyl chitosan: Guangzhou Jizhou Trading Co., Ltd.;
[0036] Tremella polysaccharide: Wuxi Jingyao Biotechnology Co., Ltd.
[0037] Examples and Comparative Examples
[0038] The present invention provides a hair care product, comprising the following components in parts by weight, as specifically shown in Tables 1-3. The preparation method of the hair care product comprises the following steps:
[0039] (1) Add the raw materials of phase A into the emulsifying pot, heat to 85±2℃, turn on the homogenizer, speed 20-30 rpm, time 3-5min, keep warm and stir until completely dissolved.
[0040] (2) Add the raw materials of phase B into the emulsifying pot, stir and heat to 85±2℃, turn on the homogenizer, speed 20-30 rpm, time 3-5 min, keep warm and stir until completely dissolved.
[0041] (3) Add the Phase C raw materials into the emulsifying pot, stir and heat to 75±2℃, turn on the homogenizer, speed 20-30 rpm, time 3-5 min, keep warm and stir until completely dissolved.
[0042] (4) Add the phase D raw materials into the emulsifier, stir and heat to 65±2℃, turn on the homogenizer, speed 20-30 rpm, time 3-5 min, keep warm and stir until completely dissolved.
[0043] (5) Add the raw materials of phase E into the emulsifying pot, cool down and stir to 55±2℃, turn on the homogenizer, speed 20-30 rpm, time 3-5 min, keep warm and stir until completely dissolved.
[0044] (6) Add the phase F raw materials into the emulsifier, cool down and stir to 45±2℃, turn on the homogenizer, speed 20-30 rpm, time 3-5 min, keep warm and stir until completely dissolved.
[0045] (7) Cool down to room temperature, inspect, unload and can.
[0046] Table 1
[0047]
[0048]
[0049] Table 2
[0050]
[0051]
[0052] Performance test-1 Anti-dandruff test
[0053] Testing is based on regulations: QTC-C-LAB-TOP-057 "In vitro test method for anti-dandruff efficacy of cosmetics (antibacterial ring method)"
[0054] Test principle: Malassezia is one of the important factors in the formation of dandruff. The growth and decline of Malassezia is directly correlated with the amount of dandruff. Malassezia furfur is a relatively in-depth study of the bacteria in the genus Malassezia. It was isolated from human dandruff (pityriasis capitis) and is representative of indicator bacteria.
[0055] In this test, the sample containing the antibacterial agent is placed on a plate stained with Malassezia furfur. The sample is continuously dissolved and diffused through the agar to form different concentration gradients to show its antibacterial effect. The size of the antibacterial ring is measured to determine whether it has antibacterial ability. It is suitable for the identification of antibacterial products containing antibacterial agents and dissolvable antibacterial (inhibitory) products.
[0056] Judgment standard: The negative control sample should not produce an antibacterial ring. If the diameter of the antibacterial ring of the test sample is >7mm, it is judged to have an antibacterial effect; if the diameter of the antibacterial ring is <7mm, it is judged to have no antibacterial effect. If there is an antibacterial effect in 3 repeated tests, it is judged to be qualified.
[0057] Test method: Take 20uL of sample (i.e., the product prepared in Examples 1-8 and Comparative Examples 1-7 of the present application), drip it onto the filter paper, dry it and set it aside: For the dissolved solid sample, make a disc with a diameter of 5mm and a thickness of no more than 4mm. Use a sterile cotton swab to take a sample with a concentration of 5.0×10 5 CFU / mL~5.0×10 6 CFU / mL Malassezia furfur suspension is evenly applied on the surface of the appropriate culture medium plate for 3 times. Place 1 infected plate for each test, 4 test samples and 1 negative control sample on each plate, for a total of 5 plates. Cover the plate, incubate at (36±1)℃ for 72h, observe the results, and measure the diameter of the inhibition ring (including the patch) with a vernier caliper and record it.
[0058] The test results are shown in Table 3, and the results are average values.
[0059] Table 3
[0060] Test Results Diameter of antibacterial ring (mm) Negative control group 0 Example 1 20.92 Example 2 19.89 Example 3 15.85 Example 4 15.84 Example 5 20.88 Example 6 17.87 Example 7 17.86 Example 8 20.81 Comparative Example 1 8.11 Comparative Example 2 8.34 Comparative Example 3 7.88 Comparative Example 4 7.89 Comparative Example 5 7.09 Comparative Example 6 7.08 Comparative Example 7 8.34
[0061] As can be seen from the above table, the anti-dandruff composition prepared by synergistically using β-glucan, carboxymethyl deacetylated chitosan, tremella polysaccharide, pyridone ethanolamine salt and PCA zinc of the present invention is applied to hair care and has a strong inhibitory effect on Malassezia furfur.
[0062] The present invention selects a system of guar gum hydroxypropyltrimethylammonium chloride, acrylic acid (ester) / acrylamide copolymer, and sodium hyaluronate as a thickener, which can better exert the inhibitory effect of the anti-dandruff composition on Malassezia furfur.
[0063] Performance Test-2 Oil Control Test
[0064] The test is based on regulations: QTC-LAB-TOP-079 "In vitro test method for oil control efficacy of cosmetics (5α-reductase inhibition method)".
[0065] Test principle: 5α-reductase (Sa-reductase) is a membrane protease that depends on reduced coenzyme II (NADPH). It is an important male hormone metabolic enzyme in the skin and can irreversibly convert testosterone (Testosterone, T) into dihydrotestosterone (Dihydrotestosterone, DHT). DHT can induce excessive oil secretion of sebaceous glands. By inhibiting the activity of 5α-reductase to reduce the level of DHT, it can effectively alleviate the excessive oil secretion of sebaceous glands. This test method is an in vitro method, which mainly evaluates the oil control effect by evaluating the inhibition rate of the test sample on the activity of 5α-reductase.
[0066] Main reagents and equipment: 5α-reductase, testosterone, NADPH, finasteride, and microplate reader.
[0067] Test method: Add PBS, testosterone solution, sample solutions or control solutions of different concentrations, enzyme extract, and NADPH solution to a 96-well plate in sequence, mix well, incubate at 37°C, and use a microplate reader to detect the absorbance change value at 340 mm within 10 minutes. Analyze and process the data to calculate the inhibition rate of the test sample on 5α-reductase.
[0068] Result calculation: 5α-reductase inhibition rate I (%) = [(ΔΑ-ΔB) / (ΔΑ-ΔC)] × 100%
[0069] Wherein: △A is the absorbance crossover value of the normal enzyme reaction group (containing PBS, testosterone solution, enzyme extract, and NADPH solution); △B is the absorbance crossover value of the experimental group (containing PBS, testosterone solution, and sample solution (sample group, i.e., the products prepared in Examples 1-8 and Comparative Examples 1-7 of the present application) / phenavirine solution (positive control group) / water (negative control group), enzyme extract, and NADPH solution); △C is the absorbance change value of the blank group (containing PBS, testosterone solution, and NADPH solution).
[0070] The test results are shown in Table 4. p<0.05 indicates that there is a statistical difference compared with the negative control group, and p≥0.05 indicates that there is no statistical difference compared with the negative control group.
[0071] Table 4
[0072] Test Results Inhibition rate of 5α-reductase (%) P-value Negative control group 0.16 / Positive control group (5ug / mL) 48.07 <0.05 Example 1 (50 mg / mL) 46.02 <0.05 Example 2 (50 mg / mL) 45.76 <0.05 Example 3 (50 mg / mL) 40.29 <0.05 Example 4 (50 mg / mL) 40.11 <0.05 Example 5 (50 mg / mL) 45.81 <0.05 Example 6 (50 mg / mL) 42.09 <0.05 Example 7 (50 mg / mL) 41.99 <0.05 Example 8 (50 mg / mL) 46.00 <0.05 Comparative Example 1 (50 mg / mL) 10.45 / Comparative Example 2 (50 mg / mL) 11.49 / Comparative Example 3 (50 mg / mL) 11.00 / Comparative Example 4 (50 mg / mL) 12.89 / Comparative Example 5 (50 mg / mL) 15.99 / Comparative Example 6 (50 mg / mL) 16.55 / Comparative Example 7 (50 mg / mL) 15.89 /
[0073] As can be seen from the above table, the anti-dandruff composition prepared by the synergistic combination of β-glucan, carboxymethyl chitosan, Tremella polysaccharide, pyridone ethanolamine salt and PCA zinc of the present invention is applied to hair care and has a very high inhibition rate on 5α-reductase.
[0074] The present invention selects a system of guar gum hydroxypropyltrimethylammonium chloride, acrylic acid (ester) / acrylamide copolymer, and sodium hyaluronate as a thickener, which can better exert the inhibitory effect of the anti-dandruff composition on 5α-reductase.
[0075] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. An anti-dandruff composition, characterized in that: The invention comprises the following components in parts by weight: 0.13-0.15 parts of beta-glucan, 0.0001-0.005 parts of carboxymethyl deacetylated chitosan, 0.0001-0.005 parts of tremella polysaccharide, 0.4-0.6 parts of pyridone ethanolamine salt and 0.12-0.15 parts of PCA zinc.
2. The anti-dandruff composition according to claim 1, characterized in that The weight ratio of the carboxymethyl deacetylated chitosan to tremella polysaccharide is (2-3):
1.
3. The anti-dandruff composition according to claim 1, characterized in that The invention also comprises the following components in parts by weight: 0.3-0.5 parts of guar hydroxypropyltrimethylammonium chloride, 0.05-0.07 parts of acrylic acid (ester) / acrylamide copolymer, and 0.07-0.09 parts of sodium hyaluronate.
4. The anti-dandruff composition according to claim 3, characterized in that The invention comprises the following components in parts by weight: 0.4-0.5 parts of guar hydroxypropyltrimethylammonium chloride, 0.07 parts of acrylic acid (ester) / acrylamide copolymer and 0.07 parts of sodium hyaluronate.
5. Use of the anti-dandruff composition according to any one of claims 3 to 4 in the preparation of hair care products.
6. A hair care product, characterized in that: Based on 100 parts by weight, the following components are included: Phase A: deionized water to make up to 100 parts by weight of each phase, 10-20 parts by weight of surfactant; Phase B: 0.4-0.6 parts of ethylene glycol distearate; Phase C: 0.3-0.5 parts of guar hydroxypropyltrimonium chloride, 0.05-0.07 parts of acrylic acid (ester) / acrylamide copolymer, 0.07-0.09 parts of sodium hyaluronate, 0.04-0.06 parts of polyquaternium-10, 0.08-0.12 parts of dipotassium glycyrrhizinate, 0.4-0.6 parts of p-hydroxyacetophenone, and 0.08-0.12 parts of phenoxyethanol; Phase D: 0.2-0.4 parts of sodium chloride; Phase E: 0.009-0.012 parts of quaternary ammonium salt-73, 0.0009-0.0012 parts of lactobacillus / soy milk fermentation product filtrate, 0.0009-0.0012 parts of purslane (PORTULACA OLERACEA) extract, 0.0009-0.0012 parts of Centella asiatica (CENTELLA ASIATICA) leaf extract; Phase F: 0.13-0.15 parts of β-glucan, 0.0001-0.005 parts of carboxymethyl deacetylated chitosan, 0.0001-0.005 parts of tremella polysaccharide, 0.4-0.6 parts of pyridone ethanolamine salt, and 0.12-0.15 parts of PCA zinc.
7. The hair care product according to claim 6, characterized in that The surfactant in phase A is at least one of sodium laureth sulfate, cocamide MEA, sodium C14-16 olefin sulfonate, sodium stearoyl lactylate, and sodium lauroyl sarcosinate; preferably, the surfactant in phase A is a mixture of sodium laureth sulfate, cocamide MEA, sodium C14-16 olefin sulfonate, sodium stearoyl lactylate, and sodium lauroyl sarcosinate, and the weight ratio is sodium laureth sulfate: cocamide MEA: sodium C14-16 olefin sulfonate: sodium stearoyl lactylate: sodium lauroyl sarcosinate = (10-15): (0.8-1.2): (0.4-0.7): (0.08-0.11): (0.08-0.11).
8. A method for preparing a hair care product according to claim 6 or 7, characterized in that: The steps include: (1) Add the raw materials of phase A into the emulsifying pot, heat to 85±2℃, turn on the homogenizer, speed 20-30 rpm, time 3-5min, keep warm and stir until completely dissolved. (2) Add the raw materials of phase B into the emulsifying pot, stir and heat to 85±2℃, turn on the homogenizer, speed 20-30 rpm, time 3-5 min, keep warm and stir until completely dissolved. (3) Add the Phase C raw materials into the emulsifying pot, stir and heat to 75±2℃, turn on the homogenizer, speed 20-30 rpm, time 3-5 min, keep warm and stir until completely dissolved. (4) Add the phase D raw materials into the emulsifier, stir and heat to 65±2℃, turn on the homogenizer, speed 20-30 rpm, time 3-5 min, keep warm and stir until completely dissolved. (5) Add the raw materials of phase E into the emulsifying pot, cool down and stir to 55±2℃, turn on the homogenizer, speed 20-30 rpm, time 3-5 min, keep warm and stir until completely dissolved. (6) Add the phase F raw materials into the emulsifier, cool down and stir to 45±2℃, turn on the homogenizer, speed 20-30 rpm, time 3-5 min, keep warm and stir until completely dissolved. (7) Cool down to room temperature, inspect, unload and can.